2020
DOI: 10.3390/metabo10070279
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell Metabolism in Atherosclerosis

Abstract: Regulatory T cells (Tregs) are capable of suppressing excessive immune responses to prevent autoimmunity and chronic inflammation. Decreased numbers of Tregs and impaired suppressive function are associated with the progression of atherosclerosis, a chronic inflammatory disease of the arterial wall and the leading cause of cardiovascular disease. Therefore, therapeutic strategies to improve Treg number or function could be beneficial to preventing atherosclerotic disease development. A growing body of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…IL-17-producing CD4+ and IL-17+ γδ + T cells are also detected in the plaques, where they likely support the development of atherosclerosis via the regulation of myeloid cell migration to the aorta and provide plaque stability via TGFβ-dependent mechanisms; however, other studies also suggest a protective role of Th17 cells [ 13 ]. T regulatory cells (Tregs) are detected in the plaques as well and their atheroprotective role is firmly established [ 14 ], whereas the role of Th2 cells remains under debate [ 12 ]. It has been suggested that atherosclerosis-prone conditions may generate various antigens that can potentially activate T cells.…”
Section: Introductionmentioning
confidence: 99%
“…IL-17-producing CD4+ and IL-17+ γδ + T cells are also detected in the plaques, where they likely support the development of atherosclerosis via the regulation of myeloid cell migration to the aorta and provide plaque stability via TGFβ-dependent mechanisms; however, other studies also suggest a protective role of Th17 cells [ 13 ]. T regulatory cells (Tregs) are detected in the plaques as well and their atheroprotective role is firmly established [ 14 ], whereas the role of Th2 cells remains under debate [ 12 ]. It has been suggested that atherosclerosis-prone conditions may generate various antigens that can potentially activate T cells.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Additionally, Baardman et al suggested that the low level of T cells and Impaired inhibition effect were related to the progress of atherosclerosis. 22 Together, atherosclerosis is a chronic inflammatory disease of the arterial wall and a major cause of cardiovascular disease. Its progression is closely related to the number and function of lymphocyte subsets, especially T cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…other microenvironmental cues, may substantially alter the T reg cells' suppressive phenotype 57,58 . Interestingly, sustained activation of T reg cells by self antigens in an inflammatory environment affects the demethylated region in the Foxp3 locus, downregulating Foxp3 expression and destabilizing T reg cells 59 .…”
Section: Box 2 | Mechanisms Of Immune-cell Accumulation In Healthy Ar...mentioning
confidence: 99%